2013
DOI: 10.1089/dna.2013.2042
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Reactivation of RANK in Glioblastoma Cells by Curcumin: Involvement of STAT3 Inhibition

Abstract: DNA methylation plays an essential role in carcinogenesis. Promoter hypermethylation can result in transcriptional silencing of specific genes, such as tumor suppressors. Thus far, few reports have investigated the effect of curcumin, an active component of the perennial herb Curcuma longa, on DNA methylation. In the present study, we evaluated the effects of curcumin on receptor activator of NF-κB (RANK) gene expression in human glioblastoma cells. Incubation of cells with therapeutic concentrations of curcum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Moreover, CUR has been demonstrated to possess direct antiangiogenic activity in vivo [ 13 15 ]. Further study showed that CUR exerted its antitumor activity involved in reactivation of receptor activator of NF-κB and inactivation of STAT3 in glioblastoma cells [ 16 ]. Additionally, CUR was discovered to suppress the cell growth through inhibition of histone deacetylase 4 (HADC4) and NF-κB pathways in medulloblastoma cells [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, CUR has been demonstrated to possess direct antiangiogenic activity in vivo [ 13 15 ]. Further study showed that CUR exerted its antitumor activity involved in reactivation of receptor activator of NF-κB and inactivation of STAT3 in glioblastoma cells [ 16 ]. Additionally, CUR was discovered to suppress the cell growth through inhibition of histone deacetylase 4 (HADC4) and NF-κB pathways in medulloblastoma cells [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Demethylation was associated with the re-activation of silenced p 16, SPARC, E-cadherin, HSP-90, and NF-κB, leading to the downregulation of DNMT-1 expression [34]. A study using U251 and U81 glioblastoma cells also showed that treatment with 30 µM curcumin for 4 days decreased the promoter hypermethylation of the receptor activator of NF-κB (RANK), resulting in RANK gene expression and activation [35]. Furthermore, in a different study, curcumin treatment in MCF-7 cells enhanced the mRNA and protein levels of Ras-association domain family protein 1A (RASSF1A) and decreased its promoter methylation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Du et al found that curcumin inhibited SHH (sonic hedgehog)/Gli1 signaling pathway, leading to inhibition of cell growth and induction of apoptosis in vitro and in vivo in glioma [ 10 ]. Further study showed that curcumin exerted its antitumor activity involved in reactivation of RANK (receptor activator of nuclear factor κB) and inactivation of STAT3 (signal transducer and activator of transcription 3) in glioblastoma cells [ 11 ]. Notably, curcumin synergistically enhanced paclitaxel-mediated cell growth inhibition in glioma cells [ 12 ].…”
Section: Introductionmentioning
confidence: 99%